Automatic Econometric Model Selection using PcGets. - Castle, J (Erasmus University Rotterdam, 2006)
Model selection is ubiquitous as we simply do not know the underlying data generating process. However, substantial criticisms are targeted at many model selection procedures. All of these criticisms can be refuted by an automatic model selection algorithms called PcGets. These algorithm is an Ox Package (see Doornik, 2001) implementing automatic general-to-specific model selection for linear regression model selections using a multi-path exploration approach: see Hendry and Krolzig (2001). This article sketches the algorithm, distinguishing between the costs of search and costs of inference. The choice of search strategy and the actual simulation performance of the algorithm are discussed and we outline the quick modeller and directions for future research.